ANALISIS PENDEKATAN EKONOMI KREATIF TIKAR PANDAN DI DESA MUNTAI KECAMATAN BANTAN KABUPATEN BENGKALIS DITINJAU DARI PERSPEKTIF EKONOMI ISLAM - Wahyuningsih, Sri (STAIN Bengkalis, 2020)
ABSTRACTAnalysis of the Creative Economy Approach of Pandanus Mat in Muntai Village, Bantan District, Bengkalis Regency in terms of Islamic Economic Perspective. Creative economy is starting to be recognized as having a very strategic role in economic development and business development. In accordance with the instruction of the President of the Republic of Indonesia No. 6 years of support for creative economy development. This support is expected to further develop towards creative economy craftsmen. There are 14 sub-sectors of the creative industry, one of which is crafts. The creative economy craft sector in Muntai Village, Bantan District, Bengkalis Regency refers to the creative economy of pandan mats. The craftsmen who produce pndan mats are housewives as an effort to improve welfare, one of which is by working on the side in order to increase family income. This research uses descriptive qualitative research. By using 15 respondents plus one collector and village officials as informants in Muntai village, Bantan district, Bengkalis district. The research method uses observation, interviews and documentation and utilizes primary data and secondary data. The main problem in this research is that it leads to the pandan mat, which is one of the traditional crafts that was formerly in great demand by the community, but over time the pandan mat craft has started to be shunned by the community. The role of the government is also very minimal in the development of this pandan mat craft so that there is no encouragement for craftsmen to activate and increase their business. Craftsmen tend to turn the pandan mat business into a side business. This study aims to determine how the creative economy approach of pandanus mats in Muntai Village, Bantan District, Bengkalis Regency and the creative economy development in Muntai Village, Bantan District, Bengkalis Regency from an Islamic economic perspective.Â Keywords: Creative Economy, Pandan Mat CraftÂ ABSTRAKAnalisis Pendekatan Ekonomi Kreatif Tikar Pandan Didesa Muntai Kecamatan Bantan Kabupaten Bengkalis Ditinjau Dari Perspektif Ekonomi Islam. Ekonomi kreatif mulai diakui memiliki peran yang sangat strategis dalam pembangunan ekonomi dan pengembangan bisnis. Sesuai dengan instruksi Presiden RI No. 6 tahun tentang dukungan pengembangan ekonomi kreatif. Dukungan ini diharapkan untuk lebih berkembang ke arah pengrajin ekonomi kreatif. Terdapat 14 subsektor industri kreatif yang salah satunya adalah kerajinan. Sektor kerajinan ekonomi kreatif yang berada pada desa Muntai Kecamatan Bantan Kabuaten Bengkalis ini merujuk kepada ekonomi kreatif tikar pandan. Pengrajin yang memproduksi anyaman tikar pndan ini meruakan para ibu rumah tangga sebagai upaya peningkatan kesejahteraan salah satunya dengan bekerja sampingan agar dapat meningkatkan pendapatan keluarga. Penelitian ini menggunakan penelitian kualitatif deskritif. Dengan menggunakan 15 orang responden ditambah dengan satu orang pengempul dan aparatur desa sebagai informan desa Muntai kecamatan Bantan Kecamatan Bengkalis. Metode penelitan menggunakan observasi,wawancara dan dokumentasi serta memanfaatkan data primer dan data sekunder. Persoalan utama dalam penelitian ini adalah mengarah pada tikar pandan yang merupakan salah satu kerajinan tradisional yang dahulunya sangat diminati masyarakat namun seiring perkembangan zaman kerajinan tikar pandan mulai dijauhi masyarakat. Peran pemerintah juga sangat minim terhadap perkembangan kerajinan tikar pandan ini sehingga tidak ada dorongan bagi pengrajin dalam menggiatkan dan meningkatkan usahanya. Pengrajin cendrung menjadikan usaha tikar pandan menjadi usaha sampingan saja. Penelitian ini bertujuan untuk mengetahui bagaimana pendekatan ekonomi kreatif tikar pandan di desa Muntai Kecamatan Bantan Kabupaten Bengkalis dan pengembangan ekonomi kreatif di desa Muntai Kecamatan Bantan Kabupaten Bengkalis ditinjau dari perspektif ekonomi Islam.Â Kata kunci : Ekonomi Kreatif, Kerajinan Tikar Pandan